2017
DOI: 10.1371/journal.pntd.0005733
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the risk of transmission of schistosomiasis in Akure North Local Government Area of Ondo State, Nigeria using satellite derived environmental data

Abstract: Schistosomiasis is a parasitic disease and its distribution, in space and time, can be influenced by environmental factors such as rivers, elevation, slope, land surface temperature, land use/cover and rainfall. The aim of this study is to identify the areas with suitable conditions for schistosomiasis transmission on the basis of physical and environmental factors derived from satellite imagery and spatial analysis for Akure North Local Government Area (LGA) of Ondo State. Nigeria. This was done through metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The criterion used to assign the scale of judgement is the strength of the hypothetical link between the risk factors and exposure. The strength of the hypothetical link was evaluated based upon three studies that evaluated the risk factors associated with schistosomiasis infection [ 47 49 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The criterion used to assign the scale of judgement is the strength of the hypothetical link between the risk factors and exposure. The strength of the hypothetical link was evaluated based upon three studies that evaluated the risk factors associated with schistosomiasis infection [ 47 49 ].…”
Section: Methodsmentioning
confidence: 99%
“…Finally, Ajakaye et al . [ 49 ] evaluated physical and environmental risk factors to identify areas with suitable conditions for schistosomiasis transmission. They used Saaty’s comparison matrix to assign weights to each risk factor.…”
Section: Methodsmentioning
confidence: 99%
“…In 2013, a nationwide mapping and prediction of schistosomiasis in Nigeria was undertaken [ 42 ]. Others have been conducted in different states of the country [ 43 , 44 ]. Few studies have also identified schistosomiasis transmission foci by mapping out areas with abundance of freshwater snails that serve of intermediate hosts of schistosomes [ 45 , 46 ].…”
Section: Schistosomiasis Mapping Efforts In Nigeriamentioning
confidence: 99%
“…The criterion used to assign the scale of judgement is the strength of the hypothetical link between the risk factors and exposure. The strength of the hypothetical link was evaluated based upon three studies that evaluated the risk factors associated with schistosomiasis infection (Ajakaye, Adedeji and Ajayi, 2017;Hu et al, 2017;).…”
Section: Construction Of Node Probability Tablesmentioning
confidence: 99%
“…As in the previous study, distance to water bodies was the most significant factor because of the smallest deviance, and elevation the least significant. Finally, Ajakaye et al (Ajakaye, Adedeji and Ajayi, 2017) evaluated physical and environmental risk factors to identify areas with suitable conditions for schistosomiasis transmission. They used Saaty's comparison matrix to assign weights to each risk factor.…”
Section: Construction Of Node Probability Tablesmentioning
confidence: 99%